Entanglement in Time: Nostalgic Affect as Cine-Choreography in The White Crow (2018) and Suspiria (2018) - Kaixuan Yao (The International Journal of Screendance, 2022)
This essay is an investigation into the historical claim of a work of screendance that involves re-imagination, re-composition, or re-enactment: In what way does it access history? And how should we treat, with due seriousness, the vicarious aura of historicity these works afford? After identifying the ontological status of time as the blind spot in the debate regarding the corporeal relationship to the archive, I introduce the Deleuzian conception of time as an incessant exchange between the virtual and the actual. I present the hauntology of certain pasts as a result of the virtual-actual exchange dissipating the temporal identity of an event, which is in turn experienced as the subject's dispersion of the self. And I redefine the body as a corporeal-archival system that channels the exchange. I then analyze the nostalgic tones of the two selected films as affects formulated by cine-choreographies that express the dispersion of the self as an experience of the dissipation of the temporal identity of an event, thereby providing an analytical approach that makes it possible to interpret such screendance practices' claim to history.
Keywords: cinechoreography; nostalgia film; Gilles Deleuze; Suspiria; The White Crow; theory of time; reenactment; time image